The Impact of Picture Card Media Oriented to Strengthening Character Education on Balinese Language Learning Outcomes in Elementary Schools - Gusti Ayu Kade Yeni Setiawati; Kadek Suranata; Kadek Yudiana (Jurnal Edutech Undiksha, 2024)
Currently, the quality of the character is decreasing. In addition, many students still need help understanding learning material. This study aims to develop a media-oriented picture card to strengthen character education on learning outcomes in Balinese for third-grade elementary school students. This research is a type of development research with the ADDIE model. The subjects of this study were 2 content experts, 2 learning designs, 2 learning media, and 2 teachers. The product trial subjects were 3 students for individual trials and 9 for small group trials. Data collection methods include document studies, rating scales, and written tests. The data collection instruments are document studies, rating scale sheets, and test questions. The data analysis techniques are descriptive qualitative analysis, quantitative descriptive analysis, and inferential statistical analysis. The study results, namely the assessment by subject content experts, are 0.94 (very high). The assessment results from learning design experts were 0.86 (very high). The results of the assessment of learning media experts are 0.94 (very high). The results of the practicality assessment given by the teacher and students obtained very good qualifications. The results of the effectiveness test show that there is a significant difference before and after using picture card media. It was concluded that picture card media was effectively used in learning Balinese.